Prawo właściwe dla licencji patentowych w polskim prawie międzynarodowym prywatnym - Sołtysiński, Stanisław (Wydział Prawa i Administracji UAM, 1987)
The Polish Act on Private International Law does not contain provisions on proper law for contracts for the transfer of technology. In the legal writings three proposals to eliminate the existing axiological lacuna have been set forth. According to the first view, if the parties did not choose the proper law, patent licences should be governed by the law proper for the seat of the exporter of technology at the moment of concluding the contract (Art. 27 § 1 sec. 1 of the Act of 1975 on Private International Law). The above solution is based on „analogiae legis" and assumes the similarity between patent licences and the contract of sale. According to the second view, in the absence of the detailed statutory regulation of the issue in question, Art. 29 of the Act, providing for the subsidiary connecting factor of the place of contract (lex loci actus), should be applied. The third view is based on the assumption that patent licences should be governed by analogous application of Art. 27 § 1 sec. 4 of the Act stipulating that for contracts for acquisition of copyrights the proper law is the law of the importer. The author declares for the latter solution. His reasoning is based on the analysis of the socio-economic function of licence contracts. Both in copyright lawas well as in patent law, the establishment of the right to exploit an invention (the author's work) is ussually based on long-term contracts, the performance of the acquirer (licensee) is of continuous character and must be fulfilled on the licence territory. Moreover, the interest of the country which is the recipient of technology prevails over the interest of the country which exports it. While the latter is interested in obtaining proceeds from the licence fees, the former sets on the licence its hopes of developing its own economy. Besides, the recipient takes much greater risk of the transaction. The importation of technology is connected with concurrent investments, the ecological risk, etc. Moreover, subjecting the licence contract to the law in force on the licence territory is the only way to prevent the conflict between „lex loci protections" and the law proper for the contractual status. In case the licence encompasses several countries, the author suggests the competence of the law of domicile of the licensee, provided that his domicile is on the territory of the country being the center of the economical exploitation of an invention. The second part of the article is concerned with an attempt to distinguish between the contractual status of the licence contract and the patent status (lex loci protectionis). The author defends the opinion that the admissibility of granting a licence and the dispositional consequences of a legal transaction come under lex loci protectionis.
Proper law for patent licences in Polish private international law